2006
DOI: 10.1038/modpathol.3800620
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic diversity of endometrial adenocarcinomas: implications for differential diagnosis

Abstract: Many endometrial adenocarcinomas, particularly those of endometrioid type, express estrogen receptors (ERs), progesterone receptors (PRs), and vimentin. This typical immunophenotype is frequently considered a standard against which others are compared when immunohistochemistry is used for differential diagnosis. We tested large numbers of endometrial cancers, enriched for high-grade tumors, to determine whether this reported immunophenotype was valid and whether expression differences between types of endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
155
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(175 citation statements)
references
References 33 publications
(44 reference statements)
14
155
0
1
Order By: Relevance
“…Strong and diffuse staining for p16 has been shown to correlate with serous morphology. [43][44][45] Some studies have suggested that p16 is a more robust marker of serous differentiation than p53, 43 although other studies have reported an expression gradient, with increasing levels of p16 staining from low-to high-grade endometrioid carcinoma, clear cell carcinoma and, finally, serous carcinoma, 45 suggesting that additional work is necessary to define relevant diagnostic cutoffs. We are aware of only one study that reports an association between p16 expression and aggressive clinical behavior specifically.…”
Section: Pfs -Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Strong and diffuse staining for p16 has been shown to correlate with serous morphology. [43][44][45] Some studies have suggested that p16 is a more robust marker of serous differentiation than p53, 43 although other studies have reported an expression gradient, with increasing levels of p16 staining from low-to high-grade endometrioid carcinoma, clear cell carcinoma and, finally, serous carcinoma, 45 suggesting that additional work is necessary to define relevant diagnostic cutoffs. We are aware of only one study that reports an association between p16 expression and aggressive clinical behavior specifically.…”
Section: Pfs -Morphologymentioning
confidence: 99%
“…We are aware of only one study that reports an association between p16 expression and aggressive clinical behavior specifically. 46 Loss of PTEN staining (or presence of PTEN mutation) has been associated with endometrioid histology and favorable clinical outcomes, 1,45,47,48 but antibodies against PTEN are notoriously difficult to work with. 49 Some studies have shown that a combination of markers including p53, p16, PTEN and PR may be superior to p53 alone in discriminating uterine serous versus endometrioid carcinoma.…”
Section: Pfs -Morphologymentioning
confidence: 99%
“…The alternative interpretation, which seems to have been adopted by other investigators, is that the expression (or 'overexpression') of p16 in endometrial carcinoma is abnormal, analogous to the situation in cervix. [47][48][49][50][51] A very wide range in p16 immunoreactivity (7-83%) has been reported in endometrial cancer, and this may be partly explained by differences in case selection, technical factors and varied definitions of 'positive' staining. It has been noted earlier that, when present, p16 immunoreactivity in endometrial carcinoma is typically focal and this may be helpful in distinguishing primary endometrial from endocervical adenocarcinomas.…”
Section: Endometrial Carcinoma Invasionmentioning
confidence: 99%
“…The mechanism of this overexpression, however, is probably different from that described in viral-related malignancies, since HPV DNA in situ hybridization has been negative in all studied cases (Chiesa-Vottero, Malpica et al 2007). ESC, it is rather linked to the inactivation of RB gene through dysregulation of the p16INK4a/cyclin D-CDK/pRb-E2F pathway (Reid-Nicholson, Iyengar et al 2006). Reid-Nicholson et al, (Reid-Nicholson, Iyengar et al 2006) reported that p16 overexpression was detected in 92% (22 of 24) of ESC cases, compared with 7% (3 of 42) FIGO grade 1and 2 EEC, and 25% (10 of 40) of FIGO grade 3 EEC cases.…”
Section: Overexpression Of P16mentioning
confidence: 95%